PERAN KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) DALAM PRAKTIK KARTEL MINYAK GORENG - Nabilla Rahmadina Hariyanti; R. Teddy Prima Anggriawan; Aldira Mara Ditta Caesar Purwanto (Lembaga Pengembangan Kinerja Dosen, 2023)
Business is a works that generates certain profits that are run with the capital used to make the business. In a business there are several important factors, one of which is the potential and business opportunities. In starting or running a business, it is not far from the thing called competition. What is meant by competition, in this topic is business competition, is the efforts of two parties/more companies, each of which is active in obtaining orders by offering the most favorable prices/conditions. One form of business competition is cartel practice. Based on the Law of the Republic of Indonesia Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, it is stated that the Business Competition Supervisory Commission is a commission established to supervise business actors in carrying out their business activities so that they do not engage in monopolies and or unfair business competition. In this study, the authors analyze the workings and roles of the KPPU in dealing with cartel practices.